Development of a Module Based on the Emo-Demo Game to Increase the Community’s Understanding of the Concept of Stunting - Wardani, Veronica Diniarti Mulyana Kusuma; Wahyuni, Sri; Nuha, Ulin (Kesmas Indonesia, 2024)
Modules are a type of printed learning material which is an innovative approach in providing health-related information involving family members as a strategy, especially mothers as the main target in Health Development Efforts. EMO-DEMO (Emotional-Demonstration) based games are an option for use in public education. This research aims to develop an EMO-DEMO game-based module based on stunting problems. The development model used is the Plomp development model with three stages, namely Premilinary research, Prototyping stage, and Assessment phase. This media development aims to see the effectiveness of the module based on the community's understanding of concepts in Kemiri Village using indicators of concept understanding used by researchers. The development results obtained a validity of 79.8% which is included in the very valid category. The practicality results obtained 92.1% which is included in the very practical criteria. The average N-gain is 0.8 in the high category, supported by the results of the community response of 89.93% which is categorized as high. This shows that the EMO-DEMO game-based module has received a positive response from its users. Keywords: Module, Emo-Demo, Concept Understanding, Stunting